Prevalence and bacterial resistance in urinary tract infections in São Luis, MA, Brazil in the period from 2005 to 2008 - Santana, Tatiana Cristina Fonseca Soares de (2012)
This study aimed to determine the prevalence and antimicrobial resistance of pathogens involved in urinary tract infections and diagnosed in a private laboratory in São Luis, MA. Were analyzed  875 (37%) positive urine cultures performed from January 2005 to June 2008. The agents found in urine cultures were separated into three major groups, Enterobacteria predominated among isolates of 85.5% of the samples ( Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Enterobacter aerogenes e Serratia marcenses ). Cocos Gram - positive ( Staphylococcus aureus, Enterococus faecalis ) and Gram negative non-fermenters ( Pseudomonas aeruginosa ) were recovered at rates of 89 (10.2%) and 38 (4.3%), respectively. The bacteria isolated were classified according to their origin: 638 (73%) in the community and 237 (27%) in the hospital. The majority of isolates showed high resistance to the drugs ampicillin, cephalothin and trimethoprim-sulfamethoxazole. Female patients were most affected with 603 (69%) of the cases. The correct diagnosis of urinary tract infections is of importance because allows appropriate treatment, thus avoiding complications andrecurrences